The Difficulties Senior High School Students in Writing Analytical Exposition Text - Meri Aprianti Nurjanah (Edu-Ling: Journal of English Education and Linguistics, 2018)
This research aimed to describe the difficulties of XI IPA 2 student of SMA N 3 Bengkulu Tengah in writing analytical exposition texts. The objective of this research was to find out the students’ difficulties in writing analytical exposition texts in the generic structure and the language feature. The method that was used in this study was a mixed method which consisted of a qualitative and quantitative approach. The data of this research were gathered from the analytical exposition writing test and interview. There are 52.78% students who got difficulties in the use of passive sentence and in the use simple present tense. Then 44.50% of students who cannot write the argument correctly. Based on the result, the researcher suggested to the teacher to pay more attention to teaching analytical exposition text. For the students, the researcher is suggesting to have more reading activity to enrich their vocabulary mastery and learn more about the use of passive sentence and the use of simple present tense in writing analytical exposition text.